2010
DOI: 10.1097/rli.0b013e3181c4f535
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Left Atrial Volumes and Function in Orthotopic Heart Transplant Recipients by Dual-Source CT

Abstract: Even if DSCT slightly overestimates left atrial volumes with respect to MRI, results remain clinically valid. Bicaval surgical technique offers improved left atrial performance compared with standard biatrial anastomosis. DSCT may be used as a reliable tool to estimate left atrial parameters in orthotopic heart transplant recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(20 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“…The agreement between MSCT and CMR was excellent, with no bias for LA min and the active emptying function (LAEF, LASV) and only a small bias when assessing LA max and reservoir function (CC). This very slight bias between modalities is in accordance with two previous studies [17,18].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The agreement between MSCT and CMR was excellent, with no bias for LA min and the active emptying function (LAEF, LASV) and only a small bias when assessing LA max and reservoir function (CC). This very slight bias between modalities is in accordance with two previous studies [17,18].…”
Section: Discussionsupporting
confidence: 93%
“…We found an average of 5 ml (2.4 ml/m 2 ) overestimation of LA max determined by MSCT compared with that measured by CMR corresponding to previously reported results [17]. A possible explanation for this overestimation is a systematic difference in delineation of the pulmonary veins between CMR and MSCT observers.…”
Section: Limitationssupporting
confidence: 78%
“…However, these are all fundamentally calculated based on an assumption in which the shape of LA is regarded as a rotating ellipse [4]. The current, real-time 3D TTE can assess LAV directly without any assumption and with more validity [7] and already compared LA volume by 3D TTE with those by currently gold standard MRI [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Leaving out the manual correction was unacceptable because the inclusion of pulmonary veins in the left atrium would constitute a larger part of the left atrium at minimal volume than by maximal volume, thus introducing a significant bias of the functional parameters. 42,43 Abadi et al 44 have found a similar difference between automatic segmentation and manual segmentation. The good agreement of LA volumes and function between MDCT and CMR are consistent with previous studies.…”
Section: Discussionmentioning
confidence: 81%
“…The good agreement of LA volumes and function between MDCT and CMR are consistent with previous studies. 42,43 LA volumes were measured larger with MDCT compared with CMR; this similarity with LV assessments is probably because of differences of the slice thickness of CMR and MDCT scans.…”
Section: Discussionmentioning
confidence: 92%